1975
DOI: 10.1152/jappl.1975.39.4.692
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of pharyngeal motor function in normal human subjects

Abstract: A need exists for accurate pressure recording of pharyngeal motor events. Results of this study indicate that accurate quantitation of pharyngeal motor activity is not possible using a water-filled catheter system, even when high infusion rates are used. An intraluminal strain gauge system, however, achieves high-fidelity recording. Quantitation of pharyngeal peristalsis using the intraluminal strain gauge system reveals peristaltic pressure amplitudes higher than those hitherto recorded. In normal subjects, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
5

Year Published

1976
1976
1998
1998

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(33 citation statements)
references
References 0 publications
4
24
0
5
Order By: Relevance
“…The oropharyngeal propulsive pressure is elevated to 60 mmHg (white arrow, L2). [14][15][16][17], electromyography [18], manometry with electromyography [19], and scintigraphy [20]. None of the aforementioned methods allows analysis of the pressure gradient in relationship to the bolus.…”
Section: Discussionmentioning
confidence: 99%
“…The oropharyngeal propulsive pressure is elevated to 60 mmHg (white arrow, L2). [14][15][16][17], electromyography [18], manometry with electromyography [19], and scintigraphy [20]. None of the aforementioned methods allows analysis of the pressure gradient in relationship to the bolus.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal, or axial, asymmetry of closing pressures within the human pharynx during swallowing was first shown by Dodds et al [2] in a study comparing infused manometry with solid state transducers. They demonstrated that the highest contraction pressures occur in the hypopharynx (1--4 cm above the UES high-pressure zone) with decreased pressures proximally in the oropharynx.…”
Section: Pharyngeal Asymmetrymentioning
confidence: 94%
“…Point sensors positioned within the UES 'drop out' of the sphincter, thereby registering an artefactual sphincter 'relaxation' [9,10]. The major disadvantage of perfusion manometry in the pharynx is its damped response rate which will underestimate the true peak amplitude of pharyngeal contractions [21]. However, there is a wide range of normal pressures in the pharynx, and a 'low'-amplitude contraction probably only has clinical significance if it falls below 60 mm Hg which is within the range accurately recorded by perfusion techniques.…”
Section: Cookmentioning
confidence: 99%